MULTIKULTURALISME: BELAJAR DARI MASYARAKAT PERDESAAN - Siburian, Robert (Masyarakat Indonesia, 2018)
Through this paper, I would like to explain how multiculturalism was implemented by the citizens in Kerta Buana village. The multiculturalism values had been implemented since the government of Indonesia located them at there. Those values of multiculturalism are important to be implemented because transmigrants who were alocated in Kerta Buana village came from various places and different religions and cultures, such as Hindu-Bali and Islam-Java came from Bali island, and Sasak-Lombok came from Lombok island. The differences had became a conflict potention if those differences fail to be managed. Public figures of each society and religion group understood on the situation, so they pushed each their group to live together with other society. Although they did not know what multiculturalism was, the values of multiculturalism had been implemented by them. We can see the multiculturalism of community in Kerta Buana village through their everyday life.